(untitled) (Research, Society and Development, 2022)
The present study aims to conduct a survey of technological and scientific information related to the production of functional fish pâté. The searches were carried out in patent documents available in the Espacenet database, using the keywords pâté AND fish AND A23L17/00, with the analysis of the data performed in Excel spreadsheets. The largest number of documents deposited was observed in 2003, with Russia being the largest depositor with 29.3% of documents. Of this total, independent inventors were applicants in 47% of the deposits. Among the documents analyzed, 39.65% deal with the product production process, 34.48% of technologies and 25.86% of products. Among the reviewed articles, 60% of the pates were well accepted among the tasters, with an acceptance rate higher than 70%. The study of scientific and technological prospecting adds important contributions to science, especially for the development of new products in the food area. Thus, from the selected patent documents it was possible to verify the absence of patent holders in Brazil on the analyzed theme demonstrating that the country needs greater investments in scientific research, despite the fact that the publication of scientific articles on the subject is observed, and this may be an opportunity for the development of innovation for the fish food sector.